Basic Quran learning applications for adult (IQRA') - Muhammad Hafezan, Omar (2015)
Basic Quran Learning Application for Adult (IQRA') is a learning application developed to assist adults (adult term in this thesis are the ones who age from 13 to 20 years old) learn to recognize hijaiyah letters and learn basic to read al-Quran. According to the observations, there are many adults who are unable to read the Quran because of various factors such as cannot recognize hijaiyah letters or do not have the basic knowledge to read the Quran because they do not have the interest to learn it. This application is specially developed to run on a smartphone or tablet that supports Android operating system. The idea to develop this app for smartphone or tablet is because the growth of the present era which almost all individuals have a smartphone or tablet that supports Android operating system. Therefore, with this application, it is hoped that it can attract these people to learn basic reading al-Quran in turn helps them to understand the basis for reading the Quran.